2002
DOI: 10.1103/physrevlett.89.205503
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a New Dense Amorphous Ice

Abstract: The detailed structure of a new dense amorphous ice, VHDA, is determined by isotope substitution neutron diffraction. Its structure is characterized by a doubled occupancy of the stabilizing interstitial location that was found in high density amorphous ice, HDA. As would be expected for a thermally activated unlocking of the stabilizing "interstitial," the transition from VHDA to LDA (low-density amorphous ice) is very sharp. Although its higher density makes VHDA a better candidate than HDA for a physical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

28
222
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(251 citation statements)
references
References 30 publications
28
222
0
1
Order By: Relevance
“…Annealing (i.e., isobaric heating) of compressed glasses is important experimentally: it has been found that it can change dramatically their properties [25,49,50]. Accordingly, we also have studied the evolution of structural order in isobarically-annealed glasses over a wide range of P .…”
Section: Discussionmentioning
confidence: 99%
“…Annealing (i.e., isobaric heating) of compressed glasses is important experimentally: it has been found that it can change dramatically their properties [25,49,50]. Accordingly, we also have studied the evolution of structural order in isobarically-annealed glasses over a wide range of P .…”
Section: Discussionmentioning
confidence: 99%
“…[6] the samples annealed at 11 and 19 kbar reached the same density upon decompression. The clear similarity of the RDF of RP decompressed from 19.5 kbar to that of VHDA recovered at p = 0 in experiment [8] manifested in the distinct peak at r = 3.37Å, very close to the first shell peak, allows us to identify this form as VHDA. Our results are thus compatible with the existence at p = 0 of a well-defined LDA state and a continuum of metastable HDA states with density below that of VHDA [11].…”
mentioning
confidence: 95%
“…Recently several new experimental results [6,7,8,9,10,11] raised new questions about the polyamorphism of ice.…”
mentioning
confidence: 99%
See 2 more Smart Citations